Resting cardiac vagal tone predicts intraindividual reaction time variability during an attention task in a sample of young and healthy adults - Williams, DeWayne P.; Thayer, Julian F.; Koenig, Julian (Psychophysiology, 2016)
Intraindividual reaction time variability (IIV), defined as the variability in trial-to-trial response times, is thought to serve as an index of central nervous system function. As such, greater IIV reflects both poorer executive brain function and cognitive control, in addition to lapses in attention. Resting-state vagally mediated heart rate variability (vmHRV), a psychophysiological index of self-regulatory abilities, has been linked with executive brain function and cognitive control such that those with greater resting-state vmHRV often perform better on cognitive tasks. However, research has yet to investigate the direct relationship between resting vmHRV and task IIV. The present study sought to examine this relationship in a sample of 104 young and healthy participants who first completed a 5-min resting-baseline period during which resting-state vmHRV was assessed. Participants then completed an attentional (target detection) task, where reaction time, accuracy, and trial-to-trial IIV were obtained. Results showed resting vmHRV to be significantly related to IIV, such that lower resting vmHRV predicted higher IIV on the task, even when controlling for several covariates (including mean reaction time and accuracy). Overall, our results provide further evidence for the link between resting vmHRV and cognitive control, and extend these notions to the domain of lapses in attention, as indexed by IIV. Implications and recommendations for future research on resting vmHRV and cognition are discussed.
Gesehen am 14.12.2020